(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The banking sector is the backbone of economic development. When a bank fails in a country, it has a negative impact on other sectors.The main objective of this paper is to assess the financial performance of selected public and private sector banks in India. The present study is used secondary data for period of five years from 2016-17 to 2020-2021the analogize the financial performance by using selected parameters namely Total Income, Total Expenditure, Net Profit, Capital Adequacy Ratio. The study is descriptive in nature, and secondary data is used for analysis.